SDG 7 requires post-growth energy sufficiency - Burke, Matthew J.; Melgar, Rigo (Frontiers in Sustainability, 2022)
• Sustainable Development Goal 7 (SDG 7) aims to achieve “energy for all” by improving energy security for the world’s poor while supporting a global transition toward low-carbon energy sources. • The aim of this policy brief is to evaluate and propose energy sufficiency as a feasible policy response to negative interactions of SDG 7, for climate (SDG 13), the biophysical environment (SDG 14 and 15), and social equity (SDG 10), when linked to the pursuit of unending economic growth (SDG 8). • Recommendations for SDG 7 target economy-wide absolute and per capita limits in overall energy use to precede adjustments in technology and behavior, thus shifting from energy excess for some to energy sufficiency for all.